Liver Histology of Male Rat (Rattus norvegicus) Feed L-Carnitine Supplement - Padmiswari, Anak Agung Istri Mas; Indrayoni, Putu; Wulansari, Nadya Treesna (Jurnal Pijar Mipa, 2024)
Obesity is a condition where the body is overweight due to fat accumulation, each exceeding 20-25% of body weight for men and women. L-carnitine is a nutrient that plays a role in transporting fat to the mitochondria to be burned and converted into energy for the body. Sufficient L-carnitine allows the body to burn fat at optimal levels. This research aims to determine the side effects of fed L-carnitine supplements against liver histology. This study used a completely randomized design (CRD) with four groups comprising six albino rats. The treatments were fed orally by distilled water 1 ml/day (Control), P1 fed by L-carnitine supplement dose 100 mg/kg body weight orally 1ml/day, P2 fed by L-carnitine supplement dose 150 mg/kg body weight orally 1ml/day, P3 fed by L-carnitine supplement dose 200 mg/kg body weight orally 1ml/day. Treatments were given to albino rats every day for 90 days. Variables observed measured were lipid degeneration, central vein dilation, and pyknotic nuclei. Data were analyzed with the statistical program (SPSS 22.0 for Windows) with One Way ANOVA. The results showed that feeding L-carnitine supplements in high doses for long periods can damage the liver cells of male rats. The microscopic liver damage statistical analysis showed significant differences (P<0.05) between the control and treatment groups.